Перша знахідка гриба Ramularia vizellae Crous в Україні - Сербо, С.В. (Івано-Франківськ : Супрун В.П., 2023)
A recently described species of micromycetes, Ramularia vizellae, has been documented in Ukraine. It was collected on the dead leaves of Acer campestre on the territory of National Nature Park “Sviati Hory” (Donetsk Region). The identification is verified by the author of the species. Problems of identification of the species and its sister taxa are discussed.
First record of fungus Ramularia vizellae Crous in Ukraine
Keywords: гриби; біорізноманіття; ДНК; баркодинг; Національний природний парк "Святі гори" (Донецька область, Україна)